2010
DOI: 10.1038/hdy.2010.41
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation of copia suppression in Drosophila melanogaster

Abstract: Transposable elements (TEs) are genomic parasites that propagate by exploiting its host reproductive machinery. However, some hosts have evolved the ability to silence TE activity, whereas others have not. We are investigating the population dynamics of TE host-silencing pathways, particularly copia long terminal repeat retrotransposon in Drosophila melanogaster. Here, we identify large effect genes involved in copia suppression by using a semi-quantitative analysis to assay levels of copia plasmids (believed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…Evidence for intraspecific variation in transposon activity and their connection to differences in host-silencing ability is consistent with the potential for silencing changes to drive TE activity and genome size evolution (Nuzhdin et al 1998;Vu and Nuzhdin 2011;Blumenstiel 2011). Furthermore, recent comparative studies in Arabidopsis further suggest species differences in host silencing may be a plausible contributor to genome size evolution.…”
Section: Re-activation Of Te Activitymentioning
confidence: 57%
See 1 more Smart Citation
“…Evidence for intraspecific variation in transposon activity and their connection to differences in host-silencing ability is consistent with the potential for silencing changes to drive TE activity and genome size evolution (Nuzhdin et al 1998;Vu and Nuzhdin 2011;Blumenstiel 2011). Furthermore, recent comparative studies in Arabidopsis further suggest species differences in host silencing may be a plausible contributor to genome size evolution.…”
Section: Re-activation Of Te Activitymentioning
confidence: 57%
“…Crosses between two species of Australian wallaby (Macropus eugenii and Wallabia bicolor) led to a large increase in the size of centromeres due to proliferation of retroelements (Waugh O'Neill et al 1998). Although transcript levels may not necessarily correlate with elevated rates of transposition, for example if posttranscriptional silencing is in place (Nuzhdin et al 1998;Vu and Nuzhdin 2011), there are examples where hybridization can also be linked to increased accumulation. Examples include the Sunfish transposon in A. thaliana×A.…”
Section: Re-activation Of Te Activitymentioning
confidence: 96%
“…Another explanation for the absence of Athila CL3 in the Y chromosome could be a specific activity of this retrotransposon family in female plants. It has been shown that genetic factors account for variation in the stability and activity of TEs including dependence on the host's genetic background [Vu and Nuzhdin, 2011]. This may suggest that a similar mechanism employing male factor(s) can regulate Athila CL3 activity.…”
Section: Discussionmentioning
confidence: 99%
“…Bursts of retrotransposition were well documented in multiple mutant lines of Arabidopsis thaliana and demonstrated stochastic and independent ability of each TE type to be activated [Tsukahara et al, 2009]. Natural variation in TE stability and ability to increase its copy number is influenced by genetic background [Vu and Nuzhdin, 2011], changes in host silencing mechanisms and/or TE virulence (evasion of silencing and the degree of TE self-regulation) [reviewed in Agren and Wright, 2011]. Owing to a duplicative mode of spread, amplification of LTR retrotransposons can lead to substantial variations in genome size in closely related species [Vitte and Bennetzen, 2006].…”
Section: Identification Of a Novel Retrotransposon With Sex Chromosommentioning
confidence: 99%
“…This is the system of control of many TEs in Drosophila as gypsy (Pelisson et al, 2007), P (Simmons et al, 2007) and I (Brennecke et al, 2008), which are usually maternally transmitted. Other elements, as copia, have a piRNA suppressor system that seems to involve spermatogenesis-specific mechanisms (Vu and Nuzdhin, 2011). In addition, when a new element was introduced, via interspecific crosses, into the genome of another species, the small interfering RNAs produced are probably incapable of completely inhibiting transcription and transposition of this element in the new host genome.…”
Section: Discussionmentioning
confidence: 99%